Phytochemical Screening and Antimicrobial Activity of Aqueous Stem Extract of Aloe vera on Some Common Pathogenic Bacteria - Baha’uddeen Salisu Dandashire; Sa’adatu Muhammad Shema (UMYU Journal of Microbiology Research)
Aloe vera is one of the most popular ethnomedicinal plants that is commonly used in treating many infectious diseases. However, the knowledge of the spectrum of antimicrobial activity of the plant and its bioactive components is still inadequate. In this study, we carried out an automated determination of phytochemical components in aqueous extract (AE) of Aloe vera whole stem by GC-MS (Gas chromatography-mass spectrometry), determined the in vitro antimicrobial activity of the extract on some common pathogenic bacteria which included Escherichia coli, Salmonella typhi, Enterococcus faecalis and Staphylococcus aureus by agar well diffusion method, and determined the minimum inhibitory concentrations (MICs) and minimum Bactericidal concentration (MBCs) by agar dilution method. The result showed that the extract has strong antimicrobial activity against all the test organisms. No resistance was observed. The range for zones of inhibition, MIC and MBC were 12.33 ± 0.33 – 28.67 ± 0.60mm, 25mg/ml – 50mg/ml and 50mg/ml – 100mg/ml respectively. The most susceptible isolate was S. typhi (MBC = 50mg/ml) and the least sensitive isolate was E. faecalis (MBC = 150mg/ml). The GC-MS of the extract revealed 9 different compounds of which 82.82% are Palmitic acid methyl ester, (7Z)-7-Tetradecenal, Palmitin, 1,2-di-, 2-aminoethyl hydrogen phosphate and Decyl hexanoate with peak areas of 34.40%, 20.48%, 15.46% and 12.48% respectively. In conclusion, Aloe vera contained many broad spectrum antimicrobially active compounds that can be further purified to produce new antimicrobial compounds that can be used in the treatment of many diseases especially those caused by S. typhi, S. aureus and E. coli.